2020
DOI: 10.3390/nu12040999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shift Work on the Eating Behavior of Police Officers on Patrol

Abstract: Recent studies indicate that the timing of food intake can significantly affect metabolism and weight management. Workers operating at atypical times of the 24-h day are at risk of disturbed feeding patterns. Given the increased risk of weight gain, obesity and metabolic syndrome in shift working populations, further research is required to understand whether their eating behavior could contribute to these increased metabolic risks. The objective of this study was to characterize the dietary patterns of police… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 77 publications
4
57
0
Order By: Relevance
“…Finally, concerning the status of participants (1 = upper and executive management vs. two police officers), we found no significant differences in the majority of the variables (Work Demands, Social Support, Flexibility-Oriented Culture, Organizational Commitment, Job Satisfaction, OCBO (all p s > 0.05), except for the variable control ( M 1 = 3.47 SD 1 = 0.63 vs. M 2 = 2.94 SD 2 = 0.82; p < 0.05). These results are consistent with previous research showing that job content is different across posts [ 25 ]. In other words, police officers encounter significantly more physical psychological threat-related events (e.g., dealing with family disputes or crises) than executive management and, subsequently, they could feel or perceive having less control over their work.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, concerning the status of participants (1 = upper and executive management vs. two police officers), we found no significant differences in the majority of the variables (Work Demands, Social Support, Flexibility-Oriented Culture, Organizational Commitment, Job Satisfaction, OCBO (all p s > 0.05), except for the variable control ( M 1 = 3.47 SD 1 = 0.63 vs. M 2 = 2.94 SD 2 = 0.82; p < 0.05). These results are consistent with previous research showing that job content is different across posts [ 25 ]. In other words, police officers encounter significantly more physical psychological threat-related events (e.g., dealing with family disputes or crises) than executive management and, subsequently, they could feel or perceive having less control over their work.…”
Section: Resultssupporting
confidence: 93%
“…In the same vein, Hagedoorn and Van Yperen suggest that control reduces fatigue in jobs with high demands, whereas high levels of social support cause high levels of intrinsic motivation, regardless of demand and control levels [ 23 ]. Empirical research showed that strain in a police officer can be referred to as high for all the abovementioned characteristics of everyday work, and so having a social source of support would be quite interesting for the institution, preventing absence and other harmful consequences [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the timing of food intake differed across the day. These findings are consistent with multiple studies that report that the timing of food intake differed, but not the amount of food consumed, across multiple shift-types [25,58,59]. Of note, the current study is the first to suggest that this pattern of altered meal timing can be found within the same shift-type when worked under different environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…POs operating at atypical times of the 24-h day and are at risk of disturbing feeding patterns. 25 On the other hand, Garbarino et al 26 indicate that occupational stress at work and sleep problems in male POs are associated with an increased diagnosis of MetS. In contrast to this, female groups showed significantly lower prevalence rates than the group of male OWs and POs.…”
Section: Discussionmentioning
confidence: 98%